Identification and Bioactivity Studies of Flavonoid Compounds from Macaranga hispida (Blume) Mull.Arg - Megawati,; Saepudin, Endang; Hanafi, Muhammad; Darmawan, Akhmad; Lotulung, Puspa Dewi N. (Makara Journal of Science, 2015)
Two flavonoid compounds, 5,7,3’,4’-tetrahydroxy-6-geranylflavonol (1) and kaempferol 7-O-β-glucose (2) have been isolated from the leaves of Macaranga hispida (Blume), Mull.Arg. Isolation and purification were conducted by chromatography methods and chemical structure characterization was carried out by spectroscopic methods. The 5,7,3’,4’-tetrahydrxyi-6-geranyl flavonol (1) and kaempferol 7-O-glucose (2) had moderate cytotoxic activity against murine leukemia P-388 cell lines with IC50 value of 0.22 and 101.5 μg/mL, respectively. The IC50 for antioxidant activities of (1) and (2) were 2.83 and 13.95 μg/mL, respectively. The LC50 of (1) and (2) from BSLT were 350 and >1000 μg/mL, respectively.